The Unit Price Implication of Reinforcement Usage in Tie Beam Reinforced Concrete Construction - Mubarak Mubarak; Tripoli Tripoli; Nurisra Nurisra (Aceh International Journal of Science and Technology, 2018)
The construction cost as one of the most important project resources should be planned and use efficiently. Cost estimation can be analysed using standard of unit price analysis according to Indonesian National Standard (SNI 7394:2008). Related to unit price analysis for tie beam reinforced concrete, the standard mentioned a specific analysis that combine all materials requirement include reinforcement (unit price analysis No. 6.29). In such analysis, reinforcement requirement is stated as much as 200 kg/m3 of concrete. Considering the diversity of dimension design of building structure caused by geographical location and building function, a further study required to response these problems. This research is aimed to provide information to what extent the unit price analysis related to tie beam reinforced concrete can be enforced in cost estimating. Research process initiated with secondary data collection to building construction located in zone 10 and 15 based on earthquake zone map (SNI 1726:2012) in Province of Aceh. The results of analysis informed that the ratio of reinforcement requirement of tie beam in zone 10 is 198.03 kg/m3 to 217.26 kg/m3 of concrete with average ratio 209.83 kg/m3. For zone 15, reinforcement requirement ratio is 203.76 kg/m3 to 233.83 kg/m3 of concrete with average ratio 215.17 kg/m3. The Potential inaccurate of cost estimation appears in the two review zones. Such inaccuracies may have an impact on the insufficient costs for the work. Thus, the use of the standard unit price analysis needs further assessment for proper application.